Uwagi o polszczyźnie północnokresowej w wileńskim druczku instructio compendiaria de accentu polonico z XVIII wieku - Lewaszkiewicz, Tadeusz; Wydra, Wiesław (Slavia Occidentalis, 2024)
The Vilnius print consists of 29 articles of varying length (from a few to more than a dozen lines), containing orthoepic notes on spelling, phonetics and partially accidence of the Polish language used in the late 17th/early 18th centuries. It is no exaggeration to state that this Latin print is the oldest Polish dictionary of correct usage. It can be of interest to researchers into Polish historical grammar. This article focuses on chapter 25 which is of special importance for the history of the Polish language spoken in Eastern Borderlands.